Endovascular Management of Anterior Cranial Fossa Dural Arteriovenous Malformations: A Technical Report and Anatomical Discussion - Mack, W.J (Centauro S.r.l., 2011)
Dural arteriovenous fistulas (dAVFs) of the anterior cranial fossa have traditionally been treated by open surgical disconnection. Safe navigation through the ophthalmic artery or fragile cortical veins has historically provided a barrier to effective endovascular occlusion of these lesions. Using current microcatheter technology and embolic materials, safe positioning within the distal ophthalmic artery, beyond the origin of the central retinal artery, is achievable. We describe two cases in which anterior cranial fossa dAVFs were treated by exclusively endovascular strategies, and highlight the pertinent technical and anatomic considerations. We discuss the clinical symptoms resulting from the differing venous drainage patterns.